2018
DOI: 10.1016/j.matdes.2017.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the mechanical and thermal properties of injection-molded polylactide parts by the addition of acrylated epoxidized soybean oil

Abstract: Enhancement of the mechanical and thermal properties of injection-molded polylactide parts by the addition of acrylated epoxidized soybean oil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 64 publications
5
63
0
Order By: Relevance
“…This phenomenon positively contributes to improving the elongation at break compared to uncompatibilized PLA‐DE composite. Regarding some previous studies, it has been observed that epoxidized or maleinized vegetable oils, such as palm oil, cottonseed oil, flaxseed oil, among others, produce a plasticizing effect in thermoplastic matrices at relatively low concentrations …”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…This phenomenon positively contributes to improving the elongation at break compared to uncompatibilized PLA‐DE composite. Regarding some previous studies, it has been observed that epoxidized or maleinized vegetable oils, such as palm oil, cottonseed oil, flaxseed oil, among others, produce a plasticizing effect in thermoplastic matrices at relatively low concentrations …”
Section: Resultsmentioning
confidence: 94%
“…Some research work shows that the addition of naturally derived maleinized oils (MLO, for example) reaches plasticizer saturation in PLA and other polyesters at a relatively low oil concentration. This leads to phase separation, which is visible as rounded shapes and hollows . In addition, a certain decrease in the gap size between the PLA matrix and diatomite particles can be observed.…”
Section: Resultsmentioning
confidence: 97%
“…Nevertheless, the efficiency of vegetable oil-based plasticizers is very poor as, in general, a very slight decrease on the glass transition temperature is achieved. Nevertheless, the highly reactive groups in modified vegetable oils (mainly epoxy, acrylate, maleic anhydride groups, among others) can react with hydroxyl groups present in the end chains of polyesters thus leading to additional reactions that could lead to chain extension, branching and crosslinking simultaneously as reported by Quiles-Carrillo and coworkers [41][42][43] in several works. With regard to Joncryl ® , typical amounts of 1 wt% are recommended by suppliers to avoid gel formation by crosslinking.…”
Section: Disintegration In Controlled Compost Soilmentioning
confidence: 99%
“…Among other renewable raw materials, soybean oil is one of the most promising starting materials for polymer synthesis which could replace petroleum‐derived monomers. It contains a high amount of unsaturated bonds which can be transformed into more reactive functional groups . Acrylated epoxidized soybean oil (AESO), containing high amount of various functional groups such as acrylic, epoxy, and hydroxy groups, is commercially available under Ebecryl 860 trademark .…”
Section: Introductionmentioning
confidence: 99%